Cross‐Link‐Functionalized Nanoparticles for Rapid Excretion in Nanotheranostic Applications. Issue 46 (2nd September 2020) - Ma, Zhuoran; Wang, Feifei; Zhong, Yeteng; Salazar, Felix; Li, Jiachen; Zhang, Mingxi; Ren, Fuqiang; Wu, Anna M.; Dai, Hongjie
Abstract: Most NIR‐IIb fluorophores are nanoparticle‐based probes with long retention (≈1 month or longer) in the body. Here, we applied a novel cross‐linked coating to functionalize core/shell lead sulfide/cadmium sulfide quantum dots (PbS/CdS QDs) emitting at ≈1600 nm. The coating was comprised of an amphiphilic polymer followed by three crosslinked amphiphilic polymeric layers (P 3 coating), imparting high biocompatibility and >90 % excretion of QDs within 2 weeks of intravenous administration. The P 3 ‐QDs were conjugated to an engineered anti‐CD8 diabody (Cys‐diabody) for in vivo molecular imaging of CD8+ cytotoxic T lymphocytes (CTLs) in response to anti‐PD‐L1 therapy. Two‐plex molecular imaging in combination with down‐conversion Er nanoparticles (ErNPs) was performed for real‐time in vivo monitoring of PD‐L1 positive tumor cells and CTLs with cellular resolution by non‐invasive NIR‐IIb light sheet microscopy. Imaging of angiogenesis in the tumor microenvironment and of lymph nodes deep in the body with a signal‐to‐background ratio of up to ≈170 was also achieved using P 3 ‐QDs. Abstract : A general strategy was developed to functionalize nanoparticles with a cross‐linked (branched PEG–linear PAA–branched PEG, P 3 ) surface coating. The P 3 coating allowed rapid excretion of nanomaterials from the body, establishing a foundation for nanomedicine‐based theranostics for clinical translation for human use.